Athapaskan clothing and related objects in the collections of Field Museum of Natural History - VanStone, James W. (Fieldiana. Anthropology, 1981)
Documents and illustrates 31 items of northern Athapaskan clothing and related objects obtained in the Yukon valley of Alaska near the end of the 19th century.